Perceptions of coastal dwellers about the effects of extreme temperature and saline water on human health: evidence from Bangladesh - Muhammad Zakaria; Muhammad Zakaria; Rezaul Karim; Rezaul Karim; Didar Islam; Md. Sarwar Ahmad; Mostak Ahammad; Feng Cheng; Feng Cheng; Junfang Xu (Frontiers in Public Health, 2025)
BackgroundClimate change disproportionately affects coastal communities worldwide, increasing exposure to extreme temperature and saline water intrusion. Understanding these impacts is critical for public health planning and intervention. This study aims to examine the perceptions about the effects of climate change-induced phenomena, specifically extreme temperature and water salinity, on the overall human health of coastal communities residing in Ramgati, Lakshmipur, Bangladesh.MethodsThe study adopted a quantitative research approach and utilized a cross-sectional survey design to gather data. The sample consisted of 391 participants (N = 391) residing in the coastal region of Ramgati. A structured questionnaire was employed to collect data. The gathered data were subjected to several bivariate analyses, including independent-sample t-tests, Pearson correlation analysis, and hierarchical regression analysis, using IBM SPSS version 24.0.ResultsParticipants exposed to higher extreme temperature reported their perceptions of various health effects, such as heat stroke, dengue epidemic, migraine and headache. Additionally, participants experiencing elevated water salinity reported different health effects, including hair loss, high blood pressure, diarrhea, maternal health problems, child development, and hindered child mental health development. Linear regression analysis revealed that participants’ age (β = 0.33, p < 0.001), gender (β = −0.16, p < 0.001), perceived risk of health diseases (β = 0.17, p < 0.001), high salinity in water (β = 0.15, p = 0.002), and high temperature (β = 0.25, p < 0.001) were significantly associated with the perception of health effects.ConclusionThis study highlights the importance of addressing key issues regarding the effects of extreme temperature and saline water on human health. Specifically, the study reports on access to clean drinking water, climate change adaptation strategies, health education and awareness, an integrated public health approach, and the needs of vulnerable populations, in order to mitigate the effects of climate change on human health living in the coastal areas.